A escrita do sudoeste: uma visão retrospectiva e prospectiva (Palaeohispanica. Review about languages and cultures of Ancient Hispania, 2019)
The last decade witnessed a substantial, though not spectacular, advancement of current knowledge about the Iron Age epigraphy of Southwest Iberia. New findings build a significant body of new text which allows a re-evaluation, contrasted with new evidence, of some of the more important aspects of the study of this epigraphy as a whole, especially the inventorying and phonetic identification of the writing system.Relevant theoretical advances, which have been presented to the academic community, put us in the way forward towards a better understanding of the realities conveyed by the epigraphs, both in the strict sense of understandings its texts and of the significance of the funerary practices in the wider social and cultural context.
Keywords: Iron Age; Epigrphy; Writing; Southwest Iberia; Writing system